The buffering effect of mental Toughness on the impact of appearance-focused social comparison on disordered eating behaviors through body dissatisfaction - DarJuan, Alyssa Marie SP (Animo Repository, 2023)
Appearance-focused social comparison is linked to the development of disordered eating behaviors. Moreover, it is shown that body dissatisfaction directly affects one’s eating patterns in a negative way. The objective of the study was to explore the relationship of appearance-focused social comparison and disordered eating behaviors with body dissatisfaction as a mediator. Furthermore, this study aimed to investigate if one’s level of mental toughness may buffer the effects of appearance-focused social comparison and the level of body dissatisfaction to the development of disordered eating behaviors. Applying a nonexperimental cross-sectional design, this was tested by examining the responses of 207 young adults within the age range of 18 – 34 using a moderated mediation analysis. The results showed that appearance focused social comparison predicted disordered eating behaviors through body dissatisfaction as a mediator. The current study revealed two interesting findings. First, mental toughness did not serve as a buffer in the relationship of appearance focused social comparison and body dissatisfaction. However, it was revealed that mental toughness acted as a buffer in the path of body dissatisfaction and disordered eating behaviors. From these findings, we can derive several theoretical and clinical implications that may contribute to the knowledge surrounding the mechanism of disordered eating behaviors and how mental toughness may help in mitigating its effects.